2016
DOI: 10.1007/s13365-016-0452-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on viral CNS inflammation beyond herpes encephalitis

Abstract: The early diagnosis of herpes simplex virus encephalitis (HSVE) enables induction of antiviral therapy in this potentially life-threatening disease. The study aimed to determine clinical findings including cerebrospinal fluid (CSF) data and MRI imaging in HSVE patients and to identify features distinguishing HSVE from encephalitis of other viral etiologies. We retrospectively reviewed consecutive patients who were diagnosed with viral encephalitis between 2000 and 2014 at the University Hospital Halle. Forty-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Diffusion weighted imaging (DWI) is used extensively to measure water proton diffusion and image inflammation in the brain or abdomen [63,64]. However, application of DWI for pulmonary imaging can allow for qualitative analysis of the signal intensity of lung defects and can give localised quantitative information about lung inflammation.…”
Section: Non-contrast Enhanced Mri In Cystic Fibrosismentioning
confidence: 99%
“…Diffusion weighted imaging (DWI) is used extensively to measure water proton diffusion and image inflammation in the brain or abdomen [63,64]. However, application of DWI for pulmonary imaging can allow for qualitative analysis of the signal intensity of lung defects and can give localised quantitative information about lung inflammation.…”
Section: Non-contrast Enhanced Mri In Cystic Fibrosismentioning
confidence: 99%
“…This should be performed before the LP. Initially computed tomography is used frequently but most important is the more sensitive magnetic resonance imaging and this should be the imaging study of choice in suspected viral encephalitis (Jordan et al, 2016;Piquet and Cho, 2016;Koeller and Shih, 2017).…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…From the largest MRI studies that focused on HSV encephalitis we can conclude that more extensive FLAIR lesions (>3 brain lobes affected) on the MRI acquired on admission are associated with higher mortality and morbidity ( 47 , 48 ). On the other hand, VZV encephalitis may well be diagnosed despite normal MRI brain scans ( 55 ); this may explain why we found no study evaluating the prognostic value of MRI in VZV encephalitis.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, other studies showed no association between MRI findings and outcome (40,55). The studies by Kim et al (40) and Jordan et al (55) both included a retrospective analysis, of 25 and 15 patients, respectively. In the study by Kim et al (40) there was a surprisingly low number of abnormal MRI (64% FLAIR and 59% diffusionweighted imaging (DWI)) compared to larger studies (32,48).…”
Section: Herpes Simplex Encephalitismentioning
confidence: 99%
See 1 more Smart Citation